The Ghosts of Epidemics Past, Present, and Future (The Hastings Center report, 1993)
Book reviewed in this article: AIDS: The Making of a Chronic Disease. Edited by Elizabeth Fee and Daniel M. Fox. Perspectives on AIDS: Ethical and Social Issues. Edited by Christine Overall and William P. Zion. AIDS in the Industrialized Democracies: Passions, Politics, and Policies. Edited by David L. Kirp and Ronald Bayer.